Use of human intra-tissue stem/progenitor cells and induced pluripotent stem cells for hair follicle regeneration - Manabu Ohyama (BMC, 2019)
Abstract Background The hair follicle (HF) is a unique miniorgan, which self-renews for a lifetime. Stem cell populations of multiple lineages reside within human HF and enable its regeneration. In addition to resident HF stem/progenitor cells (HFSPCs), the cells with similar biological properties can be induced from human-induced pluripotent stem cells (hiPSCs). As approaches to regenerate HF by combining HF-derived cells have been established in rodents and a huge demand exists to treat hair loss diseases, attempts have been made to bioengineer human HF using HFSPCs or hiPSCs. Main body of the abstract The aim of this review is to comprehensively summarize the strategies to regenerate human HF using HFSPCs or hiPSCs. HF morphogenesis and regeneration are enabled by well-orchestrated epithelial-mesenchymal interactions (EMIs). In rodents, various combinations of keratinocytes with mesenchymal (dermal) cells with trichogenic capacity, which were transplanted into in vivo environment, have successfully generated HF structures. The regeneration efficiency was higher, when epithelial or dermal HFSPCs were adopted. The success in HF formation most likely depended on high receptivity to trichogenic dermal signals and/or potent hair inductive capacity of HFSPCs. In theory, the use of epithelial HFSPCs in the bulge area and dermal papilla cells, their precursor cells in the dermal sheath, or trichogenic neonatal dermal cells should elicit intense EMI sufficient for HF formation. However, technical hurdles, represented by the limitation in starting materials and the loss of intrinsic properties during in vitro expansion, hamper the stable reconstitution of human HFs with this approach. Several strategies, including the amelioration of culture condition or compartmentalization of cells to strengthen EMI, can be conceived to overcome this obstacle. Obviously, use of hiPSCs can resolve the shortage of the materials once reliable protocols to induce wanted HFSPC subsets have been developed, which is in progress. Taking advantage of their pluripotency, hiPSCs may facilitate previously unthinkable approaches to regenerate human HFs, for instance, via bioengineering of 3D integumentary organ system, which can also be applied for the treatment of other diseases. Short conclusion Further development of methodologies to reproduce bona fide EMI in HF formation is indispensable. However, human HFSPCs and hiPSCs hold promise as materials for human HF regeneration.